2017
DOI: 10.1371/journal.pone.0176672
|View full text |Cite
|
Sign up to set email alerts
|

Periploca forrestii saponin ameliorates CIA via suppressing proinflammatory cytokines and nuclear factor kappa-B pathways

Abstract: ObjectivePeriploca forrestii Schltr has been used as a Chinese folk medicine for the treatment of rheumatism, arthralgia and fractures. However, the anti-arthritic activity of Periploca forrestii saponin (PFS) and the active compound has still not been revealed. This study aimed to investigate the protective effects and mechanisms of PFS on collagen type II (CII) collagen-induced arthritis (CIA) mice. We sought to investigate whether PFS and Periplocin could regulate osteoclastogenesis, and if so, further inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…CIA induction resulted in the development of a pronounced synovitis associated with an autoimmune response against cartilage with inflammatory cells infiltrate and production of many cytokines and matrix-degrading, accompanying cartilage degradation and bone erosions [31,32]. Our results revealed, for the first time, that Per-OL and OL supplemented diets exhibited preventive effects in the development of inflammation and joint damage in SD-CIA.…”
Section: Discussionmentioning
confidence: 51%
“…CIA induction resulted in the development of a pronounced synovitis associated with an autoimmune response against cartilage with inflammatory cells infiltrate and production of many cytokines and matrix-degrading, accompanying cartilage degradation and bone erosions [31,32]. Our results revealed, for the first time, that Per-OL and OL supplemented diets exhibited preventive effects in the development of inflammation and joint damage in SD-CIA.…”
Section: Discussionmentioning
confidence: 51%
“…In the course of inflammatory disease, NF- κ B activation controls the production of proinflammatory mediators, such as NO and its mediator protein iNOS, PGE2 and its mediator protein COX2, and cytokines IL-6 and TNF- α [ 61 ]. In the previous study, PFS was found to have inhibited the phosphorylation of p65 and its inhibitory protein (I κ B) [ 31 ]. We deservedly further investigate the inhibitory effects of PFS on this critical transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that P. forrestii saponin (PFS) inhibits murine arthritis by suppressing cytokine production, local inflammation, and systemic autoimmune responses; PFS and its active compound periplocin also inhibit osteoclastogenesis by reducing proteinases and phosphorylation of NF- κ B p65 and its inhibitory protein (I κ B) [ 30 , 31 ]. In the present study, we further affirmed the anti-AD effect of PFS using the oxazolone-induced AD-like mouse model and elucidated the underlying molecular mechanisms of its action, providing evidence of the utilization of PFS for treating AD.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen-induced arthritis (CIA) in mice was performed according to the methodology with minor changes [20]. Chicken collagen type II (CII) was dissolved in 0.1 M glacial acetic acid to a final concentration of 2 mg/ml CII, and the solution was emulsified in an equal volume of Complete Freund's Adjuvant (CFA containing 4 mg/ml mycobacterium tuberculosis) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%